Strategi Peningkatan Pendapatan Daerah Melalui Retribusi Lingkungan Di Kota Mojokerto - Handoyo, Puji Handayati; Budi Eko Soetjipto; Etty Soesilowati; Ratna Dwi Nastiti (Universitas Airlangga, 2023)
This research aims to determine the potential for increasing revenue from waste retribution in Mojokerto City as a means of increasing PAD thus it can maximize the potential of the APBD for the benefit of regional social and economic development. This is qualitative research using a descriptive case study approach. The data used is primary and secondary data collected using interview or FGD, documentation, and questionnaire methods. Data analysis was carried out using Miles and Huberman, starting from data collection, data reduction, data presentation, and conclusion. Data shows that the total revenue from waste retributions is only able to cover 5% of the total waste management costs thus the remaining 95% of these costs are charged to the APBD. Strategies are needed so that the potential for retribution revenue can be increased. The potential calculation is carried out by increasing the rates of 2x and adding household retribution data. The results show that increasing retribution rates and adding household data can increase the percentage of costs that can be covered by up to 50%. So, it can be concluded that this strategy contributes to increasing PAD. The research results are expected to have a theoretical contribution to contribution theory related to research on strategies for increasing Regional Original Income (PAD). Apart from that, it is hoped that the results of this research will have a practical contribution to the Mojokerto City Government in developing strategies to increase waste levy revenues.